The Lottery rose - Hunt, Irene (New York : Berkley Books, 1986)
A young victim of child abuse gradually overcomes his fears and suspicions when placed in a home with other boys
Reprint. Originally published: New York : Scribner's, 1976
Keywords: Child abuse -- Juvenile fiction